DISCLOSURE OF ISR AND GRI INDEX ON SHARIA BANKING IN INDONESIA - Andi Zulfikar (NISBAH: JURNAL PERBANKAN SYARIAH, 2018)
The purpose of this paper is to examine the effect of sharia governance by sharia supervisory boards and audit committees on the disclosure of the Islamic Social Reporting Index (ISRI) and Global Reporting Index (GRI). Sharia banks are currently using the Social Reporting Index (SRI) and the Global Reporting Index (GRI). These have been researched by previous research that found weaknesses sharia governance in sharia banking sector in Indonesia. This research uses quantitative method by using purposive sampling technique. Analytical techniques used are multiple regression techniques (multiple regression) and Independent Samples T-test. The results of this study found that the role of directors of sharia banks affects the disclosure with the index of ISR, while the sharia supervisory board is influential in disclosure using the GRI index. The result of independent samples T-test found that the disclosure with ISR index is higher compared to GRI index. The implications of this research are the weakness of sharia governance in sharia banking in Indonesia during the study period 2013-2016, so that this can be an input for sharia banking, Bank Indonesia, and sharia supervisory board. This research develops previous research by examining the effect of sharia governance function in optimizing disclosure with ISR and GRI index.